Mixed Conductors under Light: On the Way to Solid Oxide Photo-Electrochemical Cells. (26th April 2016) - Fleig, Juergen; Walch, Gregor; Brunauer, Georg Christoph; Rotter, Bernhard; Esmaeli, Esmaeil; Summhammer, Johann; Opitz, Alexander Karl; Ponweiser, Karl
Abstract : Photo-electrochemical cells based on aqueous electrolytes have been heavily investigated for their potential to convert light into chemical energy. In contrast, very little is known on the possibility of transferring photon energy into chemical energy in high temperature solid state electrochemical cells. This is true despite the fact that solid electrolyte based systems can be operated very successfully as fuel and electrolysis cells (SOFCs/SOECs). Here, we report results on the interaction of mixed conducting oxides with light in cells using oxide ion conductors and operating at 350-500°C. One type of system contains a high temperature solar cell based on SrTiO3 and LaCrO3 . It allows oxygen pumping and thus chemical energy storage under UV light. In another type of system UV light produces a time dependent voltage that includes two processes potentially also enabling energy storage: First, again a photovoltaic effect is present; second, the illuminated mixed conducting oxide changes its stoichiometry and thus leads to a battery type (Nernstian) voltage.